Mobile phones and microorganisms transmission in hospital environment - Odyssefs I. Botsis; Stefanos Athanasios N. Moustakis (Ene, 2018)
The use of mobile devices within the clinical setting is becoming more and more frequent. However it may involve several risks not directly visible, the results of which are more obvious. The purpose of the study was to present the risk factors responsible for hospital acquired infections, caused by the use of mobile devices within the clinical setting. In addition, the study aimed at raising public awareness of these infections in order to reduce the risk factors for patients and for the staff themselves, as well as to propose methods of prevention and management. The study reveals that half of the medical and nursing staff use their electronic devices during their visit to the patient, while more than the 2/3 of the mobile devices are colonized by pathogenic strains. It turns out that electronic devices carry several pathogenic microorganisms which are potentially harmful to the patient as well as to staff. In order to address the current problem, staff has to be more diligent and more attentive at work and steps to be taken by the healthcare facility itself.